Design of Rubrics for Technical Seminar, Industry Internships, and Projects - Dr. Arun Kumar B. R. (Handbook of Outcome-Based Education Model (OBE): Best Practices and Formats for OBE Implementation in Technical Higher Education Programs, 2023)
Rubrics defined set the clarity for students regarding the expectations of learning. In this Chapter, the importance of rubrics and their design is discussed for the course namely Technical Seminar, Industry Internship, and Projects.